Association between wearing a personal floatation device and death by drowning among recreational boaters: a matched cohort analysis of United States Coast Guard data. Issue 3 (1st October 2010) - Cummings, P; Mueller, B A; Quan, L
Abstract : Objective: To estimate the association between wearing a personal floatation device (PFD) and death by drowning among recreational boaters. Design: Matched cohort study analysis of Coast Guard data. Setting: United States. Subjects: Recreational boaters during 2000–2006. Main outcome measures: Risk ratio (RR) for drowning death comparing boaters wearing a PFD with boaters not wearing a PFD. Results: Approximately 4915 boater records from 1809 vessels may have been eligible for our study, but because of missing records and other problems, the analysis was restricted to 1597 boaters in 625 vessels with 878 drowning deaths. The adjusted RR was 0.51 (95% CI 0.35 to 0.74). Conclusions: If the estimated association is causal, wearing a PFD may potentially prevent one in two drowning deaths among recreational boaters. However, this estimate may be biased because many vessels had to be excluded from the analysis.